Resituating Erving Goffman: From Stigma Power to Black Power. Issue 4 (July 2018) - Tyler, Imogen
This article offers a critical re-reading of the understanding of stigma forged by the North American sociologist Erving Goffman in his influential Stigma: Notes on the Management of Spoiled Identity (1963). One of the most widely read and cited sociologists in history, Goffman was already famous when Stigma was published in 1963. His previous books were best-sellers and Stigma alone has sold an astonishing 800, 000 copies in the 50 years since its publication. Given its considerable influence, it is surprising how little sustained engagement there has been with the historicity of Goffman's account. This article resituates Goffman's conceptualisation of stigma within the historical context of Jim Crow and the Black freedom struggles that were shaking 'the social interaction order' to its foundations at the very moment he crafted his account. It is the contention of this article that these explosive political movements against the 'humiliations of racial discrimination' invite revision of Goffman's decidedly apolitical account of stigma. This historical revision of Goffman's stigma concept builds on an existing body of critical work on the relationship between race, segregation and the epistemology of sociology within the USA. Throughout, it reads Goffman's Stigma through the lens of 'Black Sociology', a field of knowledge that here designates not only formal sociological scholarship, but political manifestos, journalism, creative writing, oral histories and memoirs. It is the argument of this article that placing Goffman's concept of stigma into critical dialogue with Black epistemologies of stigma allows for a timely reconceptualisation of stigma as governmental technologies of dehumanisation that have long been collectively resisted from below.